(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Background: maternal nutrition and breast milk nutrient concentration are associated with infant’s growth. Enhanced knowledge encourages mothers to breast feed for the sake of optimizing growth and development. Methods: the current study was performed longitudinally in some rural areas, south of Iran, from birth to six months. Out of 319 candidates with serial anthropometric measurements of an infant, including weight, height, and head circumference at four times (birth, two, four, and six months ), 195 were included in the multivariate regression model (total measurements, n=776) to construct the pattern of growth. Then, information regarding demographic background, lactation status and infant supplementation intake status, feeding practices, maternal anthropometric measurements, and food frequency questionnaire were collected from mothers and their children during six months in two rural health centers. Results: The most important association between dietary factors and infant anthropometrics (weight, height, and head circumference) involved Factor2 vegetables, including leafy vegetables, tomato, onion and garlic, (weight β=0.35 95%CI 0.27 - 0.44, length β=3.82 95%CI 3.42 - 4.22, head circumference β=2.55 95%CI 2.32 - 2.79) and Factor1 fruit, including orange, kiwi, cherries, watermelon, date, and grapes) (weight β=0.117 95%CI 0.04-0.189, length β=0.59 95%CI 0.257-0.929, head circumference β=0.307 95% CI 0.108-0.507), respectively. Generalized Estimation Equation model revealed that Factor2 dairy (including low fat milk, yogurt and dough) significantly contributed to weight growth velocity (β=-0.009 95% CI -0.016 - 0.001). Conclusion: a dietary habit of fruit and vegetables, which are rich in bioactive components by breast feed mother showed better growth for infants. As growth is multifactorial, maternal nutrition and breastfeeding duration is a simple modifiable factor which can affect the subsequent growth and development of the child during the first six months. Key words: exclusive breastfeeding, growth, anthropometric measures, maternal nutrition, and multivariate multiple regression.